2018
DOI: 10.5505/tjtes.2018.62436
|View full text |Cite
|
Sign up to set email alerts
|

The XXXX score: A new diagnostic score for acute appendicitis

Abstract: BACKGROUND: The Karaman score is a novel diagnostic scoring system consisting of 6 parameters. The aim of the present study was to assess the diagnostic performance of the Karaman score in comparison with the Alvarado score. METHODS: A total of 200 patients who underwent an appendectomy were enrolled in the study (research registry number: 2290). RESULTS: The cutoff threshold of the Karaman score in distinguishing acute appendicitis from negative appendectomy was ≥9 with 84.3% sensitivity, 64.7% specificity, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…Karaman et al conducted a study in our city in 2018 and stated that the Karaman scoring system, which consists of six parameters, is more accurate for predicting appendicitis than the Alvarado score. However, in our study, the Karaman CSS was not superior to the other scoring systems in any age group [15]. Te relatively small sample size of our study group may be the reason why Karaman's score was not found to be superior to other scores among age groups.…”
Section: Discussioncontrasting
confidence: 80%
“…Karaman et al conducted a study in our city in 2018 and stated that the Karaman scoring system, which consists of six parameters, is more accurate for predicting appendicitis than the Alvarado score. However, in our study, the Karaman CSS was not superior to the other scoring systems in any age group [15]. Te relatively small sample size of our study group may be the reason why Karaman's score was not found to be superior to other scores among age groups.…”
Section: Discussioncontrasting
confidence: 80%
“…Timely diagnosis is critical, as delays may lead to both maternal (1-4%) and fetal (1.5-35%) mortality due to perforation of the appendix [15]. To this end, various scoring methods have been developed based on imaging studies, clinical findings, and laboratory results [16][17][18][19][20][21][22][23][24]. The present study aimed to evaluate the extent to which these scoring methods are suitable for the diagnosis of appendicitis in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In both Karaman and Alvarado scoring systems, gender is not considered when calculating the score. In their published study in 2018, they claimed that the Karaman scoring system is superior to the Alvarado score in predicting appendicitis and reducing the rate of negative appendectomy [ 7 ]. In our study, we found that the Karaman scoring system was more successful in predicting appendicitis either in male or female patient groups than scoring systems that considering gender.…”
Section: Dıscussıonmentioning
confidence: 99%
“…Ultrasound (USG) is the imaging method that should be the first choice in diagnosing appendicitis due to its lower cost, easier accessibility, and no radiation exposure compared to CT, with a sensitivity of 79% and a specificity of 87% [ 6 ]. Nevertheless, USG performed by an inexperienced radiologist with a heavy patient load, especially outside of working hours, may mislead the clinician and cause overtreatment or under treatment [ 7 , 8 ].…”
Section: Introductıonmentioning
confidence: 99%